2014
DOI: 10.1007/s12199-014-0385-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower air temperature is associated with ambulance transports and death in Takamatsu area, Japan

Abstract: Objective The aim of this study was to investigate the linkage among ambulance transports, the number of death and air temperature in Takamatsu area, Japan. Methods Monthly data of ambulance transports (total and acute disease) and the number of death from 2004 to 2012 were obtained from Fire Department Service in Takamatsu and Takamatsu city official website, Japan. Climate parameters for required period were also obtained from Japan Meteorological Agency. Population data in Takamatsu area were also used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…In addition, by quadratic curves, we estimated the relationship between total ambulance transports and climate parameters, and between the number of deaths and climate parameters. The correlation coefficients, especially between the number of deaths and climate parameters, were not as high compared with our previous reports in the Takamatsu area, which is located in Shikoku Island, Japan [10]. Southern et al [6] showed that despite the potential for significant adverse effects of snow days on the incidence of myocardial infarction, snow days had only minor effects, if any.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In addition, by quadratic curves, we estimated the relationship between total ambulance transports and climate parameters, and between the number of deaths and climate parameters. The correlation coefficients, especially between the number of deaths and climate parameters, were not as high compared with our previous reports in the Takamatsu area, which is located in Shikoku Island, Japan [10]. Southern et al [6] showed that despite the potential for significant adverse effects of snow days on the incidence of myocardial infarction, snow days had only minor effects, if any.…”
Section: Discussioncontrasting
confidence: 57%
“…We have also previously reported that lower air temperature was associated with higher ambulance transports in the Sakata area, Yamagata Prefecture, Tohoku, Japan [9]. In addition, lower air temperature was closely linked to a higher the number of deaths in the Takamatsu area, which is located on Shikoku Island, Japan [10]. However, we could not fully evaluate especially the effect of very low air temperature and snowfall on ambulance transports and the number of deaths for Japan as a whole.…”
Section: Introductionsupporting
confidence: 53%
“…We previously reported a significant relationship between air temperature and the total number of deaths, but not the number of deaths stratified by causes in Sakata city [17], Takamatsu city [18], Asahikawa city [19], and all 47 prefectures of Japan [20]. The number of ambulance transports was found to be associated with air temperature, and lower air temperature (winter season) was also closely associated with a higher total number of deaths [17][18][19][20]. Therefore, an effective strategy to prevent deaths affected by air temperature is required in Japan.…”
Section: Introductionmentioning
confidence: 87%
“…We performed 2 studies; First, to confirm the association between ambulance transports and meteorological data, we performed a retrospective and statistical analysis similar to the previous reports. 6 , 7 Second, we made prediction models for daily ambulance transports using meteorological and calendarial factors and evaluated their accuracies to test the utility of the DL-based models.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, weather, or meteorological factors are related to ambulance dispatches, the number of deaths, and traumas. [2][3][4] Also, the total numbers of deaths have a relationship with air temperatures, [5][6][7][8] and winter also relates to trauma like fractures 9 and motor vehicle accidents. 10 However, there are 4 seasons in Japan with meteorological flections.…”
Section: Introductionmentioning
confidence: 99%